Penerapan Kebijakan Pemerintah Dalam Penentuan Harga Jual Gula Kristal Putih Melalui Peraturan Menteri Perdagangan Republik Indonesia Nomor 7 Tahun 2020 - Mahruf Mahruf (Universitas Nasional, 2022)
The Regulation of the Minister of Trade of the Republic of Indonesia Number 7 of 2020 concerning Reference Purchase Prices at the Farmer Level and Reference Sales Prices at the Consumer Level is the legal basis for government policies in regulating the reference purchase price at the farmer level and the reference selling price at the consumer level. In its application, not as a reference price but as a maximum limit or the highest retail price, especially the price of white crystal sugar (GKP), thus making sugarcane farmers and business actors not have legal certainty. The reference price for sugar commodities is always seen from the global sugar price where the price has actually been distorted so that it cannot be used as a benchmark for Indonesian domestic prices where sugarcane plantations and the national sugar factory industry must compete freely without any government protection, so that unfair business competition will lead to unfair competition. kill sugarcane plantations and national sugar mills. This research is an empirical juridical research, which examines the applicable legal provisions and what happens in reality in society. Data collection techniques were obtained from interviews with questionnaires, library research and legislation. The results of this study indicate that the Regulation of the Minister of Trade of the Republic of Indonesia Number 7 of 2020 concerning Reference Purchase Prices at the Farmer Level and Reference Sales Prices at the Consumer Level only regulates the reference price for purchasing white crystal sugar at the farmer level and selling prices at the consumer level, not regarding retail prices. the highest price limit, and the determination of the maximum price for the purchase and sale of white crystal sugar is detrimental to sugar cane farmers and business actors of white crystal sugar. Peraturan Menteri Perdagangan Republik Indonesia Nomor 7 Tahun 2020 tentang Harga Acuan Pembelian di Tingkat Petani dan Harga Acuan Penjualan di Tingkat Konsumen adalah landasan hukum kebijakan pemerintah dalam mengatur harga acuan pembelian di tingkat petani dan harga acuan penjualan di tingkat konsumen. Dalam penerapannya nyatanya bukan sebagai harga acuan namun sebagai batas maksimal atau harga eceran tertinggi terutama harga Gula Kristal Putih (GKP). Hal demikian membuat para petani tebu dan pelaku usaha tidak memiliki kepastian hukum. Harga acuan komoditas gula selalu dilihat dari harga gula global yang mana harga tersebut sebenarnya telah terdistorsi sehingga tidak dapat digunakan sebagai patokan harga dalam negeri Indonesia dimana perkebunan tebu dan industri pabrik gula nasional harus bersaing bebas tanpa ada perlindungan pemerintah, sehingga persaingan usaha yang tidak adil akan mematikan perkebunan tebu dan pabrik gula nasional. Penelitian ini adalah penelitian yuridis empiris, yaitu mengkaji ketentuan hukum yang berlaku serta apa yang terjadi dalam kenyataannya dalam masyarakat. Tehnik pengumpulan data diperoleh dari wawancara, penelitian kepustakaan dan perundang-undangan. Hasil penelitian ini menunjukkan bahwa Peraturan Menteri Perdagangan Republik Indonesia Nomor 7 Tahun 2020 tentang Harga Acuan Pembelian di Tingkat Petani dan Harga Acuan Penjualan di Tingkat Konsumen khususnya komoditas gula hanya mengatur harga acuan pembelian gula kristal putih di tingkat petani dan harga penjualan di tingkat konsumen, bukan tentang Harga Eceran Tertinggi, dan penentuan batas maksimal harga pembelian dan penjualan gula kristal putih merugikan petani tebu dan pelaku usaha gula kristal putih.